A Study on Retraining in the Light of Technological Changes & Up Gradation from a Global Perspective With Special Emphasis on the Chinese Economy - Naidu, Sujeesha (Prabandhan: Indian Journal of Management, 2011)
Economic conditions have a direct impact on the Human resources development initiatives that are undertaken by the government of that country. The technology era has led to many changes in the way HRM functioned in various organizations. The current study tries to take a look at retraining function of HRM due to technological changes and up gradations from a global perspective. However, the example of the Chinese economy and the innovative strategies adopted by them in order to keep abreast with the changing times is one of its kind and thus becomes an appropriate one for this study. Through this study, the author tries to point out the positive as well as negative impact of technological changes.